Comparing Quasi-Parallel and Quasi-Perpendicular Configuration in the Terrestrial Magnetosheath: Multifractal Analysis - Gurchumelia, Alexandre; Sorriso-Valvo, Luca; Burgess, David; Yordanova, Emiliya; Elbakidze, Khatuna; Kharshiladze, Oleg; Kvaratskhelia, Diana (Frontiers in Physics, 2022)
The terrestrial magnetosheath is a highly turbulent medium, with a high level of magnetic field fluctuations throughout a broad range of scales. These often include an inertial range where a magnetohydrodynamic turbulent cascade is observed. The multifractal properties of the turbulent cascade, strictly related to intermittency, are observed here during the transition from quasi-parallel to quasi-perpendicular magnetic field with respect to the bow-shock normal. A standard coarse-graining technique has been used to evaluate the generalized dimensions Dq and the corresponding multifractal spectrum f(α). A p-model fit provided a quantitative measure of multifractality and intermittency, to be compared with standard indicators: the width of the multifractal spectrum, the peak of the kurtosis, and its scaling exponent. Results show a clear transition and sharp differences in the intermittency properties for the two regions, with the quasi-parallel turbulence being more intermittent.